2023
DOI: 10.5213/inj.2346110.055
|View full text |Cite|
|
Sign up to set email alerts
|

Transfer Learning for Effective Urolithiasis Detection

Abstract: Purpose: Urolithiasis is a common disease that can cause acute pain and complications. The objective of this study was to develop a deep learning model utilizing transfer learning for the rapid and accurate detection of urinary tract stones. By employing this method, we aim to improve the efficiency of medical staff and contribute to the progress of deep learning-based medical image diagnostic technology.Methods: The ResNet50 model was employed to develop feature extractors for detecting urinary tract stones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Next, the issue contains 2 studies focusing on AI applications. Choi et al [ 4 ] reported on the application of an AI technology known as “transfer learning” that aids in efficient stone detection in patients suffering from urolithiasis. The authors carried out a verification process for this AI technology, affirming its ability to detect urolithiasis with a high degree of accuracy and confirming its viability for use within the medical field.…”
mentioning
confidence: 99%
“…Next, the issue contains 2 studies focusing on AI applications. Choi et al [ 4 ] reported on the application of an AI technology known as “transfer learning” that aids in efficient stone detection in patients suffering from urolithiasis. The authors carried out a verification process for this AI technology, affirming its ability to detect urolithiasis with a high degree of accuracy and confirming its viability for use within the medical field.…”
mentioning
confidence: 99%